Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1148/radiol.2015150489
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Small Pulmonary Nodules with Ultrashort Echo Time Sequences in Oncology Patients by Using a PET/MR System

Abstract: ).q RSNA, 2015 Purpose:To investigate the utility of a free-breathing ultrashort echo time (UTE) sequence for the evaluation of small pulmonary nodules in oncology patients by using a hybrid positron emission tomography (PET)/magnetic resonance (MR) imaging system and to compare the nodule detection rate between UTE and a conventional three-dimensional gradient-recalled-echo (GRE) technique. Materials and Methods:In this HIPAA-compliant, institutional review board-approved prospective study, 82 pulmonary no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 16 publications
7
106
1
3
Order By: Relevance
“…In addition, recent results of national lung cancer screening trials as well as previously reported results of CT-based lung cancer screenings have led to a growing need for management of pulmonary nodules in routine clinical practice. [15][16][17][18][19][20][21][22] Two major MR sequences have come into use in this setting: the turbo spin-echo (SE)-based technique and the gradient-echo (GRE) technique, with varying results for reduction of cardiac-and respiratory-motion artifacts. [9][10][11][12] For these reasons, pulmonary nodule detection and characterization on MRI has become an important diagnostic tool for pulmonary diseases and has been tested extensively during the last few years.…”
Section: Pulmonary Nodule Detectionmentioning
confidence: 99%
“…In addition, recent results of national lung cancer screening trials as well as previously reported results of CT-based lung cancer screenings have led to a growing need for management of pulmonary nodules in routine clinical practice. [15][16][17][18][19][20][21][22] Two major MR sequences have come into use in this setting: the turbo spin-echo (SE)-based technique and the gradient-echo (GRE) technique, with varying results for reduction of cardiac-and respiratory-motion artifacts. [9][10][11][12] For these reasons, pulmonary nodule detection and characterization on MRI has become an important diagnostic tool for pulmonary diseases and has been tested extensively during the last few years.…”
Section: Pulmonary Nodule Detectionmentioning
confidence: 99%
“…To overcome the size effect, a free-breathing ultrashort echo time (UTE) sequence has been evaluated in patients having small metastatic lung nodules. UTE sequence showed a higher detection rate for lung nodules with small size, non-FDG avid, not-subpleural location (p < 0.001) [66]. On the other hand, one study reported that post-contrast VIBE sequence images of MRI could not improve detection rate of pulmonary nodules more than non-contrast VIBE images (jackknife alternative freeresponse receiver-operating-characteristics value of 0.848 vs. 0.837, respectively) [67].…”
Section: Lung Cancermentioning
confidence: 99%
“…Diğer taraftan FDG tutulumu göstermeyen ve MR görüntülemede saptanamayıp sadece BT görüntülerinde izlenen nodüllerin çok büyük bir kısmının (%96.4) takipte kaybolduğu ya da stabil seyrettiği, dolayısıyla benign karakterde olduğu gösterilmiştir (67). Küçük akciğer nodüllerinin MR ile görüntülenmesini sağlamak amacıyla UTE (ultrashort echo time) gibi özel sekanslar geliştirilmiştir (68). Ayrıca hibrid PET/MR sistemlerinde, toraksın PET ve MR görüntülemeleri eş zamanlı olarak yürütüldüğünden, PET görüntüsünde solunum hareketleri için düzeltme işlemi MR görüntülemeden yararlanarak yapılabilir.…”
Section: Pet Görüntüleme Teknolojisinde Gelişmelerunclassified